Marriage Is Scary and Gen Z’s Marriage Readiness: A Sadd al-Dharā'iʿ Perspective - Nur Isna Maulidya Putri; Siti A’isyah (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
The Marriage Is Scary phenomenon among Generation Z has emerged as a socially constructed perception shaped by continuous exposure to digital narratives surrounding marriage. This phenomenon has contributed to an increasing tendency to postpone marriage, which, at the societal level, is reflected in the declining marriage rate observed in recent years. However, such postponement should not be interpreted as a rejection of marriage; rather, it represents a cautious and reflective process through which young people seek to ensure their psychological, emotional, and social readiness before entering marital life. This study examines the influence of the Marriage Is Scary phenomenon on Generation Z's marriage readiness through the lens of Sadd al-Dharā'iʿ as a normative framework in Islamic law. Employing a qualitative descriptive-analytical approach, the study draws on interviews with university students living in two contrasting social environments: an open environment characterized by intensive social media exposure and an Islamic boarding school (pesantren) environment where social media use is more closely regulated. The findings reveal that the Marriage Is Scary phenomenon primarily affects psychological and social dimensions of marriage readiness without fostering anti-marriage attitudes. Among Generation Z raised in religious environments, the phenomenon is instead internalized as a means of cultivating prudence and strengthening preparedness for marriage. From the perspective of Sadd al-Dharā'iʿ, the phenomenon can be understood as a condition requiring preventive management to avoid potential social harm (mafsadah) while simultaneously promoting the realization of marital welfare (maṣlaḥah) in accordance with the objectives of Islamic law (maqāṣid al-sharīʿah). Consequently, this perspective encourages Generation Z to develop greater readiness to navigate the challenges of married life and to establish families founded upon social values and the Islamic ideal of a sakinah, mawaddah, and raḥmah marriage